2016
DOI: 10.1371/journal.pntd.0004564
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Cryptosporidiosis in a Longitudinal Study of Slum-Dwelling Bangladeshi Children: Association with Severe Malnutrition

Abstract: BackgroundCryptosporidiosis is a common cause of infectious diarrhea in young children worldwide, and is a significant contributor to under-five mortality. Current treatment options are limited in young children. In this study, we describe the natural history of Cryptosporidium spp. infection in a birth cohort of children in Bangladesh and evaluate for association with malnutrition.Methodology/Principal FindingsThis is a longitudinal birth cohort study of 392 slum-dwelling Bangladeshi children followed over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
94
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 45 publications
17
94
3
Order By: Relevance
“…Overcrowding has been associated with Cryptosporidium infection, specifically with Cryptosporidium huminis. 26 A high secondary infection rate (39%) was reported in households with children diagnosed with Cryptosporidium infection. 27 In the present study, we found a significant association between having more than five family members and Cryptosporidium infection.…”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding has been associated with Cryptosporidium infection, specifically with Cryptosporidium huminis. 26 A high secondary infection rate (39%) was reported in households with children diagnosed with Cryptosporidium infection. 27 In the present study, we found a significant association between having more than five family members and Cryptosporidium infection.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens testing positive for Cryptosporidium were further speciated using the LIB3 assay to distinguish C. hominis from non-C. hominis isolates (12). The polymorphic region within the gp60 gene was used to genotype Cryptosporidium positive samples using previously described methods at the University of Virginia with the modifications of Alves et al (9,11). Serum samples were tested for the presence of anti-Cryptosporidium IgG, using enzyme-linked immunosorbent assay with whole Cryptosporidium coated plates (2.5x10*6 oocysts/ml) (WATERBORNE Inc., New Orleans, LA), as described in (13).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…In prior studies, we have described infection rates as high as 80% with cryptosporidiosis during the first two years of life (9). However, the route of transmission of cryptosporidiosis remains elusive since Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Cryptosporidium parvum and C. hominis are the main causative agents of cryptosporidiosis, which is the second major cause of death in children under 5 years old with diarrhea in developing countries (Kotloff et al., ). In addition, infection with Cryptosporidium has been shown to cause stunted growth in children (Kirkpatrick et al., ; Korpe et al., ; Kotloff et al., ). Despite the significance and the consequences that this parasite has for both human and animal health, until recently there have been no tools to study the biology of Cryptosporidium in the laboratory, and most research has been dependent on animal models (Sharling et al., ).…”
Section: Introductionmentioning
confidence: 99%